Morphological aspects and seasonal changes of some planktonic ciliates (Protozoa) from a temporary pond in Buenos Aires Province, Argentina - Kuppers, Gabriela Cristina (2006)
The morphology of some planktonic ciliates in a temporary freshwater pond located in Buenos Aires province, Argentina, is compared and the seasonal variation in their abundances over an annual cycle is described. Samples were taken from June 2004 to June 2005. Physical and chemical characteristics of the environment were also recorded. Taxonomic identifications were made in vivo and after employing the Protargol technique. Five planktonic species were recorded for the first time in South America.